Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica Rapa Chineensis L) Akibat Pemberian Plant Growth Promoting Rizobacteria (PGPR) Dari Akar Bambu dan EM4 - Muhammad Iqbal; Farida Hariani; Aisyah Lubis (Jurnal Agrofolium, 2026)
Pakcoy is a type of green vegetable that is still in the same group as mustard greens. Pakcoy mustard greens are also often called spoon mustard greens because their shape resembles a spoon. To improve pakcoy plants there are several things that must be considered such as fertilizer application. This study aims to determine the effect of Pgpr from bamboo roots and Em4 and the interaction of the two fertilizers on the growth and production of pakcoy plants (Brassica rapa chineensi L). The study was conducted on Jl. Tuntungan 1, Pancur Batu District, Deli Serdang Regency, North Sumatra Province. From April to May 2025. This study used a Factorial Randomized Block Design method with 2 factors studied and 3 replications. The first variable is Pgpr From Bamboo Roots (P) which has four levels, namely P0 (Control), P1 (150 ml plot-1), P2 (300 ml plot-1), P3 (450 ml plot-1). The second variable was EM4 (E), which consisted of three levels: E0 (Control), E? (10 ml liter-1 of water plot-1), and E2 (15 ml liter-1 of water plot-1). Observed parameters included plant height (cm), number of leaves (leaflets), root volume (ml), weight per sample (g), and weight per plot (g). The results showed that the administration of Pgpr from bamboo roots and Em4 had no significant effect on all observed parameters: plant height increase, leaf number increase, root volume increase, plant weight increase/sample, and plant weight increase/plot